Prior Alliances with Targets and Acquisition Performance in Knowledge-Intensive Industries - Zaheer, Akbar; Hernandez, Exequiel; Banerjee, Sanjay (Organization Science, 2010)
An important focus of the research on mergers and acquisitions is the conditions under which acquisitions create value for the acquiring firm's shareholders. Given that the acquisition process is plagued by serious issues of information asymmetry, which are exacerbated in the context of knowledge acquisitions, we examine whether prior alliances with potential targets reduce the information asymmetry enough to create “partner-specific absorptive capacity” and yield superior stock returns on acquisition, compared with acquisitions not preceded by alliances. We test our hypotheses on a sample of high-technology acquisitions by U.S. firms during 1990–1998 using an event study methodology to assess abnormal stock returns. We find, unexpectedly, that no significant general effect emerges for acquisitions with prior alliances. However, international acquisitions following alliances show significantly better returns relative to both acquisitions without prior alliances and domestic acquisitions. Additionally, stronger forms of prior alliances lead to better acquisition performance than weaker forms of alliances. Together, the results broadly support our thesis that partner-specific absorptive capacity may be at work and suggest that under certain prior alliance conditions, acquisitions can indeed create value for acquirers.